A Review of Approaches for Steganography - Arora, Komal; Gandhi, Geetanjali (International Journal of Computer Sciences and Engineering, 2014)
Steganography is the art and science of hiding communication; a steganographic system thus embeds hidden content in unremarkable cover media so as not to arouse an eavesdropperï¿½s suspicion. Many different carrier file formats are used, but digital images are the most popular because of their frequency on the internet. For hiding secret information in images, there exist a large variety of steganographic techniques some are more complex than others and all of them have respective strong and weak points. Different applications have different requirements of steganography technique used. For example, some applications may require absolute invisibility of the secret information, while others require a larger secret message to be hidden. This paper intends to give an overview of image steganography, its uses and techniques. It also attempts to identify the requirements of a good steganographic algorithm and briefly reflects on which steganographic techniques are more suitable for which applications.